UPDATE MANAGEMENT OF DENGUE COMPLICATION IN PEDIATRIC - Soegijanto, Soegeng (Institute of Topical Disease, 2011)
Dengue virus infection is one of the important health problems in Indonesia, although the mortality rate has been decreased but many dengue shock syndrome cases is very difficult to be solving handled. It might be due to nature course of dengue virus infection is very difficult to predict of the earlier time of severity occur. THE AIM To get idea to make update management of dengue complication in pediatric. MATERIAL AND METHOD Data were compiled from Dr. Soetomo Hospital Surabaya in 2009. The diagnosis of all cases was based on criteria WHO 1997 and PCR examination in Institute Tropical Disease for identified serotype of dengue virus infection. The unusual cases of dengue virus infection were treated following the new WHO protocol in 2009. RESULT There were only 3 cases with serotype DEN 1, consisted 2 cases had age 1â4 years and 1 had age 5â14 years. 2 cases showed a severe clinical performance as dengue shock syndrome and 1 case showed as unusual case of dengue virus infection. Three report cases of: a. Dengue hemorrhagic fever grade III which liver involvement and had bilateral pleural effusion; b. Dengue hemorrhagic grade III with liverÂ involvement and encephalopathy; c. Dengue hemorrhagic grade III with liver involvement acute kidney injury, myocardial involvement and encephalopathy. All the patients were treated according to new edition WHO protocol and all of the involving organ recovered along with the improvement of the disease. CONCLUSION Update management of dengue complication pediatric should be learned carefully used for helping unusual cases of dengue virus infection.